Pengaruh Kepemimpinan Kepala Madrasah terhadap Efektivitas Manajemen Pendidikan Islam di Madrasah Aliyah negeri 4 Karawang - Nurazizah, Aulia Putri; Maryati, Mimin; Munafiah, Nida'ul (Peneliti.net, 2025)
This research investigates the influence of the leadership of the madrasa head on the effectiveness of Islamic education management at Madrasah Aliyah Negeri 4 Karawang. The research method uses interview instruments to collect data from madrasa heads. The results of the analysis show that the participatory and inclusive leadership style applied by the madrasa head has contributed significantly to the development of innovative curricula, improving the quality of education, and efficient resource management. Programs such as